A Detailed Study on the Floral Biology and Fruiting of Cycad circinalis in Nigeria - J. O. Odewale; Agho Collins; E. I. Eziashi (Recent Research Advances in Biology Vol. 7, 2021)
The Cycas circinalis was first officially introduced into Nigeria by the Nigerian Institute for Oil Palm Research (NIFOR), Benin City. Cycas circinalis has adapted well as an ornamental crop in Nigeria. It belongs to the Division: Cycadophyta, Class: Cycadopsida, Order Cycadales, family Cycadaceae and genera Cycas. It was first recognized as a separate species in 1995. It is also known as Sago palm, Fern palm, Cycad or Starch palm. The floral biology of the plant is cone like as other cones in the Order Cycadales, the cone has the whorl of premature pinnate fronds embedded within the cone. This cone opens up and spreads out as the inflorescence reaches anthesis revealing the whorl of young leaves that will form the new generation crown. The mean number of fully formed fruits per stalk is 9.0 average fruit length is 5.24 cm, fruit circumference ranged from 8.6-9.6 cm while the average circumference is 9.03. Fruit weight range between 19.2 – 22.10 g (mean = 21.6 g), the length of dehusked fruit vary from 4.1 – 5.0 cm, while the circumference of the dehusked fruit range between 7.1 – 8.0 cm. The average circumference of dehusked fruit was 7.53 cm. The weight of the dehusked fruit range between 9.7– 18.6 g, with a mean weight of 13.9 g.